POLEMICS OF LEGAL SANCTIONS AGAINST CORRUPTION IN INDONESIA - Husin Wattimena; La Jamaa; Muis Saifuddin Anshori Pikahulan (Universitas Nurul Jadid, 2025)
The practice of power mentioned as not siding with the people and which is not fair is manifested in the form of actions that are detrimental to the state such as collusion, corruption and nepotism which are increasingly rampant everywhere. The Criminal Act of Corruption which has become a current political issue since the past until now, has become the government's concern and also our common concern to be overcome. The birth of Law Number 3 of 1971, followed by Law Number 28 of 1999, amended by Law Number 31 of 1999 then amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, became the basis for handling corrupt behavior in Indonesia, however all of these laws and regulations are considered unable to overcome the conditions of corrupt practices. On this basis, it is used as the focus of this study, the aim is to realize welfare and justice for all people, these noble ideals, require the best legal system to overcome it. This study is desired as a manifestation of efforts to improve the applicable legal system. The improvement of the legal system is intended, with the hope of overcoming corrupt practices that occur in order to improve the bureaucratic service system that is clean and free from nepotism, collusion, corruption as desired by the people.